Association Between Arterial Stiffness and Heart Failure With Preserved Ejection Fraction - Chi, Chen; Liu, Yifan; Xu, Yawei; Xu, Dachun (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular diseases are the leading cause of mortality in the world. Heart failure with preserved ejection fraction (HFpEF) accounts for about half of all heart failure. Unfortunately, owing to the lack of understanding of mechanisms, the effective treatment of HFpEF is still unclear, leading to no decline of morbidity and mortality of HFpEF. Arterial stiffening is the decrement of arterial compliance. The media of large arteries degenerate in both physiological and pathological conditions. A number of studies have proven that arterial stiffening is an independent risk factor for cardiovascular disorders including diastolic dysfunction. In this perspective, we discussed if arterial stiffening is related to HFpEF, and the mechanisms of how arterial stiffening contributes to HFpEF. Finally, we briefly summarized current treatment strategy on arterial stiffening and HFpEF. Though some new drugs were developed, the safety and effectiveness were not adequately assessed. New treatment strategies for arterial stiffening and HFpEF are urgently needed.